Interpretation of structures on Menapo Sungai Melayu II, The Muarajambi National Cultural Heritage Area: Use of the Wenner Configuration Method: Interpretasi struktur di Menapo Sungai Melayu II, Kawasan Cagar Budaya Nasional Muarajambi: Penerapan Metode Konfigurasi Wenner - Muhammad Rifqi; Ira Kusuma Dewi; Irsyad Leihitu (BRIN, 2023)
Menapo Sungai Melayu II is located in the Muarajambi National Cultural Heritage Area. The study aims to determine the layer and structure under the surface based on the value of resistivity. The measurements of resistivity configuration are conducted by Werner’s method. Six trajectories are placed around the using flat base electrodes to minimize the risk of damaging the structure. Based on the measurements, there are three kinds of soil formations. The resistivity value that ranging from 1,07–3,84 Ωm is indicated as water-saturated sand, the value of 4,95–13,8 Ωm is indicated as sand clay, while the highest resistivity with a value of 17,84–49,90 Ωm is interpreted as a brick. The six cross-sections have an average resistivity value of around 1,07-49,90 Ωm which indicates a brick structure that exists below the surface. Based on the results of the resistivity method, some patterns can be interpreted as main structure, as roving fence, and gateway.